Disulfide bond formation in microtubule-associated tau protein promotes tau accumulation and toxicity in vivo. Issue 21 (17th June 2021) - Saito, Taro; Chiku, Tomoki; Oka, Mikiko; Wada-Kakuda, Satoko; Nobuhara, Mika; Oba, Toshiya; Shinno, Kanako; Abe, Saori; Asada, Akiko; Sumioka, Akio; Takashima, Akihiko; Miyasaka, Tomohiro; et al.
Abstract: Accumulation of microtubule-associated tau protein is thought to cause neuron loss in a group of neurodegenerative diseases called tauopathies. In diseased brains, tau molecules adopt pathological structures that propagate into insoluble forms with disease-specific patterns. Several types of posttranslational modifications in tau are known to modulate its aggregation propensity in vitro, but their influence on tau accumulation and toxicity at the whole-organism level has not been fully elucidated. Herein, we utilized a series of transgenic Drosophila models to compare systematically the toxicity induced by five tau constructs with mutations or deletions associated with aggregation, including substitutions at seven disease-associated phosphorylation sites (S7A and S7E), deletions of PHF6 and PHF6 * sequences (ΔPHF6 and ΔPHF6 * ), and substitutions of cysteine residues in the microtubule binding repeats (C291/322A). We found that substitutions and deletions resulted in different patterns of neurodegeneration and accumulation, with C291/322A having a dramatic effect on both tau accumulation and neurodegeneration. These cysteines formed disulfide bonds in mouse primary cultured neurons and in the fly retina, and stabilized tau proteins. Additionally, they contributed to tau accumulation under oxidative stress. We also found that each of these cysteine residues contributes to the microtubule polymerization rate and microtubule levels at equilibrium, but none of them affected tau binding to polymerized microtubules. Since tau proteins expressed in the Drosophila retina are mostly present in the early stages of tau filaments self-assembly, our results suggest that disulfide bond formation by these cysteine residues could be attractive therapeutic targets.